PEMANFAATAN RUANG TERBUKA HIJAU BAGI MASYARAKAT KOTA PEKANBARU - Kurnia Rukmini; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Green open space is a space wchich is filled by the herbs and plants that are able to accommodate human activity in an environment. As for the research conducted in this study is housed in open green space of Putri Kaca Mayang at Jenderal Sudirman street of Pekanbaru. The purpose in this research is to find out how the utilization of green open space for the people of the city of Pekanbaru, i.e. as seen from the aspect of leisure as a means of entertainmentand and as a means of exercise. Furthermore, there are factors that can be the catalyst and a barrier for visitors in visiting the open green space. The theory used is a social exchange theory of George C. Humans. This type of research using quantitative descriptive approach with 75 samples as respondents from taking engineering quota sampling. The data collected by the data collection techniques in the form of questionnaires, observation and documentation. Research results in the field say the park is beneficial as a recreational park entertainment with 93.3%, 6.7% less useful, and category doesn’t rewarding 0.0%. based on the utilization of children as a means of sports by category often do sports on site research thet is 17.3%, 45.3% rarely do sports and 37.3% never do sports on site grounds. The driving factor in visiting the garden for visitors that is 50.6% over a garden layout of a combination to factors and strategic factors in the garden free of charge. restricting of factor, jammed around the garden in the afternoon and a separate garden form factor.Keywords : utilization, green open spaces, driving factor and factor inhibitor.